Kinetics of drying Bactris gasipaes Kunth sub-products: comparison of mathematical models - Velasquez-Rivera, Jorge; Melendez, Jesus R.; Roca-Argüelles, Manuel G.; Rodríguez-Sánchez, José L. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The industrialization of the heart of palm (palm heart), obtained from the sprout of a palm known as pejibaye, chontaduro, or peach palm (Bactris gasipaes Kunth), generates two main products: the fruit and the heart of the stem. The stem produces a highly perishable residue due to its high humidity, making drying an alternative to increase its useful life. The main objective of this study was to describe which of the selected mathematical models conform to better drying kinetics in samples (by-product) of palm heart (palm heart), according to the selected statistical criteria. Mathematical Modeling of the by-product drying curves (the heart of palm) was performed at two working temperatures (70 and 80 °C) and two groups, one minced and the other ground. The results of the water content were statistically processed to find the most convenient model among those proposed by other researchers. The calculation of the parameters of the different drying models was carried out with the STATISTICA version 8.0 program, using the non-linear estimation tool, according to the quasi-Newton algorithm estimation method. The results show that the models MR = exp(-k.tn) and MR = exp(-(k.t)n), called Page and modified Page respectively, were the best fit to the experimental data in all cases. Therefore, the models named Page and modified Page best fit the innovative information and the most suitable model.